(untitled) (Jurnal Manajemen Bisnis, 2025)
This study aims to analyze the influence of affective commitment, organizational support, and job satisfaction on the innovative behavior of employees of the Yogyakarta City Environmental Service. This study uses a quantitative approach with a positivistic paradigm. The research sample consisted of 50 permanent employees selected through purposive sampling techniques. The data collection instrument was a Likert scale questionnaire 1–5 which had been tested for validity and reliability. The data were analyzed using multiple linear regression techniques with the help of SPSS software. The results showed that affective commitment (p = 0.000, t = 9.635) and organizational support (p = 0.002, t = 3.199) had a positive and significant effect on innovative behavior. However, job satisfaction did not have a significant effect (p = 0.019, t = -2.433). Simultaneously, the three independent variables had an influence of 76.5% on employee innovative behavior. These findings emphasize the importance of strengthening emotional commitment and organizational support in order to increase innovative capacity in the public sector work environment.